A double-blinded randomized controlled trial of silymarin for the prevention of antituberculosis drug-induced liver injury - Luangchosiri, Chote (BMC Complement Altern Med, 2015)
BACKGROUND: Hepatitis is a common adverse effect of antituberculosis drugs. Silymarin prevented drug-induced hepatoxicity in animals with anti-oxidative mechanisms but its effect in human has been unknown. We aimed to evaluate the efficacy of silymarin for preventing antituberculosis-drug induced liver injury (antiTB-DILI) in patients with tuberculosis. METHODS: A double-blind randomized placebo-controlled trial was performed. Tuberculosis patients were randomly allocated to receive placebo or silymarin. The outcomes of interests were antiTB-DILI and the maximum liver enzymes at week 4. Antioxidative enzymes (i.e., superoxide dismutase (SOD), glutathione and malondialdehyde assays) were assessed. The risks of antiTB-DILI between the two groups were compared. A number need to treat was estimated. RESULTS: A total of 55 out of 70 expected numbers of patients were enrolled. There were 1/27 (3.7 %) and 9/28 (32.1 %) patients who developed antiTB-DILI in the silymarin and the placebo groups. Risk reduction was 0.28 (0.10, 0.47), i.e., receiving silymarin was 28 % at lower risk for antiTB-DILI than placebo. This led to prevention of 28 patients from being antiTB-DILI among 100 treated patients. Median (IQR) of ALT levels at week 4 in the placebo and the silymarin group were 35.0 (15, 415) IU/L and 31.5 (20, 184) IU/L (p = 0.455). The decline of SOD level at week 4 in the silymarin group was less than the placebo group (p < 0.027). CONCLUSIONS: Silymarin reduced the incidence of antiTB-DILI. The benefit of silymarin may be explained from superoxide dismutase restoration. Larger clinical trials are required to confirm the result of our small study [Clinicaltrials.Gov Identifier Nct01800487].